Polycythemia Vera: New Diagnostic Concept and Its Types - AM Kovrigina; VV Baikov (Клиническая онкогематология)
Polycythemia vera (PV) is a clonal Ph-negative myeloproliferative disorder characterized by excessive myeloid proliferation of three hematopoietic cell lineages leading to ineffective myelopoiesis. According to WHO classification (2008), hemoglobin and hematocrit values are listed among the major diagnostic criteria. However, in many PV patients the levels may be below the diagnostic level, thus leading to underdiagnosis of PV. At present, three clinical types of the disease are recognized: 1) masked (latent/prodromal), 2) classic (overt), and 3) PV with progression/transformation into myelofibrosis. The masked form is most difficult for diagnosis, being highly heterogeneous with regard to clinical manifestations, laboratory data, medical history, and the course of the disease. It includes early stages, some of them with very high platelet count, imitating essential thrombocythemia, cases with abdominal thrombosis, and latent PV. Bone marrow trephine biopsy appears to be the most reliable method for diagnosis of masked PV. Findings typical for PV are readily visible, including hypercellular bone marrow with three-lineage myeloid proliferation, excess of megakaryocytes with mild to moderate cellular atypia and polymorphism. Gradi